An investigation into factors affecting intervention fidelity of differentiated instruction in primary schools of Bahir Dar city administration - Tadesse Merawi (College of education, Bahir Dar University, 2023)
The main purpose of this study was to investigate the main factors affecting the intervention fidelity of DI in primary schools of Bahir Dar City Administration, Ethiopia. The study also explored the influencing power of those factors in ranked order. For this study, a convergent parallel mixed methods design was utilized and data were collected from randomly selected ten primary schools. The main findings of the study revealed that the knowledge gaps of teachers; lack of training, lack of conducive environment and scarce school resources, low motivation and commitment of teachers and school leadership; large number of student diversity, inflexible curriculum structure, lack of parental support for the students' learning, and weak staff collaboration were the major deterring factors affecting the execution of DI in terms of their order of influence.